Augmentation of Wind Farms Ride Through by DFIG-based Variable Speed Wind Generators - Okedu, K.; Muyeen, S.M.; Takahashi, R.; Tamura, J. (2012)
Wind farm grid codes require wind generators to ride through voltage sags, which means that normal power production should be re-initiated once the nominal grid voltage has been recovered. Doubly Fed Induction Generator (DFIG) based wind farm is gaining popularity these days because of its inherent advantages like variable speed operation and independent controllability of active and reactive power over conventional Induction Generator (IG). This paper proposes a new control strategy using DFIGs for stabilizing a wind farm composed of DFIGs and IGs. Simulation analysis by using PSCAD/EMTDC shows that the DFIGs can effectively stabilize the IGs and hence the entire wind farm through the proposed control scheme by providing sufficient reactive power to the system.